2016
DOI: 10.1038/jp.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord cleansing with chlorhexidine in neonates: a systematic review

Abstract: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the efficacy of chlorhexidine application to the umbilical cord in neonates. We searched MEDLINE and other electronic databases, and included all RCTs that evaluated the effect of single or multiple chlorhexidine cord applications on the neonatal mortality rate (NMR) and/or the incidence of systemic sepsis and omphalitis. A total of six RCTs—four community-based cluster RCTs and two hospital-based trials—were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
(77 reference statements)
2
14
0
1
Order By: Relevance
“…This might indicate the importance of antimicrobial agents contained in HBM or CHX. This nding was in alignment with systematic review conducted by Sankar et al that revealed a signi cant reduction in the incidence of omphalitis in infants who received the intervention; CHX [20]. The literature reviewed by Mullany et al from a developing country like southern Nepal in comparing 4.0% CHX, soap-and-water solution and dry cord care showed a signi cant reduction of incidence of mild and severe omphalitis in DCC and CHX group.…”
Section: Discussionsupporting
confidence: 76%
“…This might indicate the importance of antimicrobial agents contained in HBM or CHX. This nding was in alignment with systematic review conducted by Sankar et al that revealed a signi cant reduction in the incidence of omphalitis in infants who received the intervention; CHX [20]. The literature reviewed by Mullany et al from a developing country like southern Nepal in comparing 4.0% CHX, soap-and-water solution and dry cord care showed a signi cant reduction of incidence of mild and severe omphalitis in DCC and CHX group.…”
Section: Discussionsupporting
confidence: 76%
“…For preterm birth related complications, the focus is on antenatal corticosteroids and provision of quality NICU care including oxygen, continuous positive air pressure and surfactant. Whereas, to combat sepsis the focus is on asepsis [20,21], chlorhexidine cord care (in areas with high NMR) [22,23], appropriate use of antibiotics, and topical emollient (natural plant oils) treatment for hospitalized infants [24]. Other interventions like exclusive breastfeeding, kangaroo care, thermoregulation, etc., influence both.…”
Section: Discussionmentioning
confidence: 99%
“…However, data is lacking on the effectiveness of chlorhexidine in a setting where the NMR is < 30/1000 live-births as well as for in-hospital deliveries [7, 8]. Globally, there are two important questions: 1) do the beneficial effects of chlorhexidine application warrant a change in the current recommendation of “dry cord care” (without chlorhexidine) in newborn infants [9]?, and 2) is the application of chlorhexidine as effective in the hospital setting as it is in the community setting?. Three trials from South Asia (Nepal [10], Bangladesh [11] and Pakistan [12]) found a reduction in neonatal mortality, while studies from Sub-Saharan Africa (Zambia [13] and Tanzania [14]) did not.…”
Section: Introductionmentioning
confidence: 99%